COMPARATIVE ANALYSIS OF SOUT H KOREAN AND JAPANESE FOREIGN DIRECT INVESTMENT IN INDONESIA'S TEXTILES INDUSTRY IN 1990Sx - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
Since early New Order, Japan and other Asia Newly Industrializing Countries have become the most important source countries of foreign direct investment (FDI) in Indonesia. While Japan was in the top rank of the Top Ten Investors during 1967-1999 in the cumulative of realized projects and values, South Korea emerged as the second most important investors regarding the cumulative number of realized projects. In 1990-1998, the cumulative of total approved values of South Korean FDI reached newly one third ofJapanese FDI's in the same period. It is interesting to know that according to Extended Dimension of Kojima Hypothesis, Japanese FDI in 1990s has characteristics similar to developed countries FDI while South Korean FDI in 1990s has characteristics similar to Japanese FDI when Japan was still a developing country. The characteristic differences may give different impact and benefit to their technology and trade performances in the host country. This study examined what similarities and differences exist between South Korean and Japanese FDI in Indonesia's textiles industry in 1990, in terms of their investment characteristics. Investment characteristics involve technology level, trade dependencies and orientation, investment contribution, investment size, ownership distribution, subindustry dist ribulion and employment generation. This study was aimed to look at whether South Korean and Japanese FDI characteristics in Indonesia's textiles industry in 1990s fit with Extended Dimension of Kojima Hypothesis. Comparative analysis was used as a means to examine the industry level and the firer level data of 17 Japanese EDI and 35 South Korean EDI in Indonesia's textiles industry ( including gatmen1). This present studvfound that, in technology performances point of view, Japanese EDI showed higher labor produciivityâykill intensity and capital intensity than that of South Korean 11)1. In trade performances point of view. Japanese EDI's export and import proportions were loiver than that ofSouth Korean EDI. South Korean FDIlvas more dependent on foreign market and foreign raw material compared to Japanese EDI. These findings indicate that Japanese EDI used relatively higher technology level than South Korean EDI and had less trade motivation both in export and import. On the other hand. South Korean EDI used relatively lower technology level than Japanese EDI and had more trade motivation than Japanese 1:01. The whet-findings reveal that though South Korean EDI had ât relatively smaller investment value per project. it had generated more employment than Japanese EDI. Ownership distribution showed that both South Korean and Japanese EDI tended to invest with majority-owned status as the first preference. Whole-owned status sras the second most preferred status for South Korean FD! while Japanese chosen minority-owned status. The findings of this study clearly supports Extended Dimension of Kojima Hypothesis that in 1990s South Korean EDI characteristics reflects developing country EDI and Japanese [Dl characteristics reflects developed country ED1.